(untitled) (International Journal of Physiotherapy, 2019)
Background: Neural mobilization (NM) constitutes the most effective, common method for assessing and treating several neuromuscular disorders. The study at hand aims to determine the effectiveness of the NM technique compared to lumbar stabilization exercise (LSE) and Radial Extracorporeal Shock Wave Therapy (rESWT) in the physical therapy management of chronic low back pain (CLBP) with radiculopathy. Methods: Two groups comprising 30 participants and randomly chosen formed the basis of this investigation: Group A (NM, LSE, and rESWT) and Group B (LSE and rESWT). The period of three to six weeks constituted the time it took to measure the results herein reached baseline. The results of the observations focused on pain assessed by numerical pain rating scale (NPRS), Lumbar flexion range of motion (Lumbar FROM) by Schober’s method, and disability level as measured by the Modified Oswestry Disability Questionnaire (MODQ). Results: In the control group, the mean scores of pain, lumbar FROM, and MODQ at baselines showed a high level of similarity (6.47, 2.87, and 43.71 respectively in the intervention group, and 6.20, 2.93 and 44.66. Both groups showed improvement in their pain scores at three weeks (P<0.05). However, only lumbar FROM and MODQ showed statistically significant improvement in favor of the intervention group at three weeks (P<0.05). By week 6, both groups achieved a statistically significant difference in the values of all variables. Conclusion: NM with LSE and rESWT is more effective than LSE and rESWT in the third week, and was similarly effective in the sixth week of the treatment. NM with LSE and rESWT may be an alternative treatment option in the treatment of CLBP.